Budgetary Choices And Public Finance Sustainability İn Morocco: Empirical Evaluation - Toufik, Said; El Baghdad, Saad (European Scientific Journal, ESJ, 2016)
This article is designed to measure public finance sustainability in Morocco, to analyze the strength of the relationship between public revenue and expenditures by assessing the quality of budgetary choices. In the light of the results, output budgeting remains a pillar that allows the Moroccan Government to make significant macroeconomic performance.